MODEL PELATIHAN KESIAPAN KERJA BERBASIS GREEN SKILLS UNTUK MENYIAPKAN LULUSAN MEMASUKI DUNIA KERJA - Pramudia, Joni Rahmat; Ilfiandra; Purnomo; Mutamam, Mohamad Hadi Ali; Yulinda; Pradikto, Bayu (Jurnal Obor Penmas: Pendidikan Luar Sekolah, 2025)
This study examines the green skills-based job readiness training model to prepare graduates to enter the workforce in order to overcome the challenges of the transition to new environmentally friendly jobs through the Research & Development method or abbreviated as R & D, with a mixed methods approach (quantitative and qualitative) which aims to find an effective green skills-based job readiness training model to prepare graduates to enter the workforce, especially in various environmentally friendly job schemes. Through in-depth interviews, FGDs and questionnaires, this study found that respondents realized the importance of green skills-based job readiness training, felt its benefits, and showed a positive attitude towards the developed training model. The conceptual training model is based on rational aspects, assumptions, objectives, principles, strategies, procedures, competencies and success indicators. Meanwhile, the implementation of the training model refers to six main steps, namely getting started, planning, generation and evaluation of green productivity options, implementation of green productivity options, monitoring and review, and sustaining green productivity.